Oral History Program Interview: J. R. McClintock - McClintock, J. R.
McClintock was born in 1915 in Winnett, Petroleum County, Montana. He came to Hanford, California in October 1934. His interview includes his family's surviving the collapse of the markets for livestock and produce, why churches were important, his claim that unions did not organize where he worked, his unawareness that people lived like those characterized in The Grapes of Wrath, how the WPA complicated getting work, and how the CCC was a great program.